2020
DOI: 10.1016/j.xcrm.2020.100033
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibodies Protect against Oral Transmission of Lymphocryptovirus

Abstract: SUMMARY Epstein-Barr virus (EBV) is a cancer-associated pathogen for which there is no vaccine. Successful anti-viral vaccines elicit antibodies that neutralize infectivity; however, it is unknown whether neutralizing antibodies prevent EBV acquisition. Here we assessed whether passively delivered AMMO1, a monoclonal antibody that neutralizes EBV in a cell-type-independent manner, could protect against experimental EBV challenge in two animal infection models. When present prior to a high-dose intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(80 citation statements)
references
References 76 publications
1
79
0
Order By: Relevance
“…Previous study found that EBV lacking gH failed to infect both epithelial cells and B cells 50 , which indicates the indispensable role of gH in EBV infection. As expected, the human neutralizing antibody AMMO1, which binds to gH/gL D-I to D-II, can block EBV infection of both B cells and epithelial cells 34,35 , but the precise mechanism of neutralization was unknown. These results suggest a potential gH/gL receptor that might be used during EBV infection of epithelial cells and B cells.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Previous study found that EBV lacking gH failed to infect both epithelial cells and B cells 50 , which indicates the indispensable role of gH in EBV infection. As expected, the human neutralizing antibody AMMO1, which binds to gH/gL D-I to D-II, can block EBV infection of both B cells and epithelial cells 34,35 , but the precise mechanism of neutralization was unknown. These results suggest a potential gH/gL receptor that might be used during EBV infection of epithelial cells and B cells.…”
Section: Discussionmentioning
confidence: 54%
“…Reagents: Peptides based on amino acids 1 to 50 of R9AP, including R9AP 1-12 (MAREECKALLDG), R9AP [13][14][15][16][17][18][19][20][21][22][23][24] (LNKTTACYHHLV), R9AP [19][20][21][22][23][24][25][26][27][28][29][30] (CYHHLVLTVGGS), R9AP [30][31][32][33][34][35][36][37][38][39][40][41] (SADSQNLRQELQ), and R9AP [35][36][37][38][39][40][41][42][43][44][45][46] (NLRQELQKTRQK), as well as a scrambled control peptide (LVHYTHCGSLGV) were synthesized by CHINESE PEPTIDE (China). The rabbit anti-R9AP antibody used for Western blotting (WB), immuno uorescence staining and immunohistochemistry staining w...…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…And in the humanized mouse model, AMMO1 showed excellent neutralizing ability against EBV infection of lymphocyte populations. However, 72A1, which was thought to be a neutralizing antibody targeting gp350, failed to prevent EBV-driven changes and reduce the viral load in humanized mice ( 26 ). Bu et al found that antibodies to EBV gH/gL play an important role in epithelial-cell and B-cell-neutralizing titers against EBV infection in human plasma ( 16 ).…”
Section: Discussionmentioning
confidence: 99%